Los equinodermos (Echinodermata) del arrecife de Cabo Pulmo, Pacífico de México - Cintra Buenrostro, Carlos E (1998)
A systernatic list of the echinoderrns from Cabo Pulmo reef, Pacific coast of México (23.5° N), is presented. Data were obtained from field surveys (1986 to 1993), and comp1emented with 1iterature searches. A total of 38 species have been reported at Cabo Pulmo, but only 25 of them were actual1y observed in the reef during our visits. This finding suggests that cornmunity structure and composition have changed in important ways since 1943, date of the first reports of echinoderrns for the locality.